VCAM-1 expression is upregulated by CD34+/CD133+-stem cells derived from septic patients. - Christian Patry (PLoS ONE, 2018)
CD34+/CD133+- cells are a bone marrow derived stem cell population, which presumably contain vascular progenitor cells and are associated with improved vascular repair. In this study, we investigated whether the adhesion molecules ICAM-1 (intercellular adhesion molecule-1), VCAM-1 (vascular adhesion molecule-1), E-selectin und L-selectin, which are involved in homing of vascular stem cells, are upregulated by CD34+/CD133+-stem cells from septic patients and would be associated with improved clinical outcome. Peripheral blood mononuclear cells from intensive care unit (ICU) patients with (n = 30) and without sepsis (n = 10), and healthy volunteers (n = 15) were isolated using Ficoll density gradient centrifugation. The expression of VCAM-1, ICAM-1, E-selectin and L-selectin was detected on CD34+/CD133+-stem cells by flow cytometry. The severity of disease was assessed by the Simplified Acute Physiology Score (SAPS) II. Serum concentrations of vascular endothelial growth factor (VEGF) and angiopoietin (Ang)-2 were determined by Enzyme-linked immunosorbent assay. The expression of VCAM-1, ICAM-1, E-selectin and L-selectin by CD34+/CD133+-stem cells was significantly upregulated in septic patients, and correlated with sepsis severity. Furthermore, high expression of VCAM-1 by CD34+/CD133+-stem cells revealed a positive association with mortalitiy (p<0.05). Furthermore, significantly higher serum concentrations of VEGF and Ang-2 were found in septic patients, however none showed a strong association with survival. Our data suggest, that VCAM-1 upregulation on CD34+/CD133+-stem cells could play a crucial role in their homing in the course of sepsis. An increase in sepsis severity resulted in both and increase in CD34+/CD133+-stem cells and VCAM-1-expression by those cells, which might reflect an increase in need for vascular repair.